(untitled) (European Journal of Economics, Finance and Business Development, 2025)
This article is devoted to socioeconomic aspects of investment security, investment security indicators, economic theories on investment security, criteria for evaluating the investment climate, and issues of providing investment security in the Republic of Uzbekistan.